Draft Tribal Sub-Plan 2006-2007 - Planning Commission (Planning Commission, 2006)
The Constitution of India provides the framework for safeguarding and protecting the interest of Scheduled Tribes (ST). While ensuring equity and social justice,in the planned process of development, the issue of differential vulnerability of the deprived sections of the society needs to be addressed continuously and adequately. In view of high poverty and unemployment amongst the tribal population formulation and implementation of development programmes in the TSP area assumes greater importance. All departments have been instructed, everything else being equal, to give preference to ST individual beneficiaries and ST tolas, in respect of scheme which are individual and tola/village based and provide adequate economic and social infrastructure for their all round development.
Planning and Development Department Government of Jharkhand Ranchi